The Text-Belief Consistency Effect Among Recent Upper Secondary Graduates: An Eye Tracking Study - Mariola Giménez-Salvador; Ignacio Máñez; Raquel Cerdán (MDPI AG, 2024)
Readers tend to allocate more cognitive resources to processing belief-consistent than belief-inconsistent information when reading multiple texts displaying discrepant views. This phenomenon, known as the text-belief consistency effect, results in individuals being more prone to making biased decisions and falling victim to manipulation and misinformation. This issue is gaining relevance due to the undeniably vast amount of information surrounding us. Hence, schools must ensure that students complete their education prepared to face this challenge. However, international surveys and research indicate a generalized literacy deficiency among students. In the present study, recent upper secondary graduates read four texts discussing a controversial topic to explore whether they effectively overcome the text-belief consistency effect or not. Eye tracking was used to explore immediate (or passive) and delayed (or strategic) text processing, and an essay task was used to measure their resulting mental representation of the text content. Results revealed no significant differences in immediate and delayed processing depending on whether the arguments were belief-consistent or belief-inconsistent. Moreover, essays displayed a balanced and unbiased approach to the debate. Despite these results suggesting this population may be capable of overcoming the text-belief consistency effect, limitations in the study and alternative explanations must be explored before drawing definite conclusions.